No Increased Risk of Spinal Cord Ischemia in Delayed AAA Repair Following Thoracic Aortic Surgery. (February 2013) - Ullery, Brant W.; Wang, Grace J.; Woo, Edward Y.; Cheung, Albert T.; McGarvey, Michael L.; Carpenter, Jeffrey P.; Fairman, Ronald M.; Jackson, Benjamin M.
Objective: To examine the results of open or endovascular abdominal aortic aneurysm (AAA) repair following prior open or endovascular thoracic aortic surgery. Methods: A retrospective review of all patients who underwent AAA repair in a delayed fashion following prior thoracic aortic surgery at a single university hospital between 1999 and 2011 was performed. Results: Thirteen patients underwent AAA repair following prior thoracic aortic repair. Mean age was 68.9 ± 6.9 years and 77% (n = 10) were male. Three patients experienced transient delayed-onset spinal cord ischemia (SCI) following initial thoracic surgery. Mean time interval between initial thoracic aortic surgery and subsequent AAA repair was 2.0 ± 1.8 years. Overall rate of SCI and 30-day mortality after delayed AAA repair was 0%. Conclusions: This series does not demonstrate any evidence of increased risk of perioperative mortality or SCI in patients undergoing delayed AAA repair after prior thoracic aortic surgery.